Menangkal Radikalisme Agama Berdasarkan Paradigma Misi Kristen Yang Berlandaskan Doktrin Allah Trinitas - Alvary Exan Rerung (Sekolah Tinggi Teologi Aletheia, 2023)
The reality of the number of radicalism in Indonesia is news that creates a dilemma for the diversity in it. In Christianity itself, religious radicalism is also evident when reading the pattern of Christian missions which is based on the text of the Great Commission as an order for Christianity. This pattern of mission also makes other religions increasingly suspicious of Christianity. They are wary of such a pattern of Christian teachings. Especially in Christianity, many say that such a mission is what Jesus wants according to his command in the great commission. Seeing this reality, an effort is needed to be able to see whether these teachings are still in line with the values of Pancasila and the 1945 Constitution which uphold tolerance. This paper uses descriptive qualitative methods and a literature study approach in providing answers to these problems. This paper offers a pattern of Christian missions based on the doctrine of God the Trinity as an effort to counter religious radicalism. This mission pattern sees missions centered on the Trinitarian God and leaves the mission pattern based on the Church. This mission will provide values of tolerance and will be a shield in countering religious radicalism in Indonesia.Realitas angka radikalisme di Indonesia merupakan berita yang membuat dilema bagi kemajemukan yang ada di dalamnya. Pada agama Kristen sendiri, radikalisme agama juga nyata ketika membaca pola misi Kristen yang berlandasakan pada teks amanat agung sebagai perintah kristenisasi.Â Pola misi ini juga yang membuat agama-agama lain semakin mencurigai agama Kristen. Mereka was-wasa terhadap pola ajaran agama Kristen yang demikian. Apalagi dalam agam Kristen banyak yang mengatakan misi yang seperti itulah yang Yesus kehendaki sesuai dengan perintahnya dalam amanat agung. Melihat realitas tersebut, maka diperlukan usaha untuk dapat melihat ajaran-ajaran tersebut apakah masih sejalan dengan nilai Pancasila dan UUD 1945 yang menjunjung tinggi toleransi. Tulisan ini menggunakan metode kualitatif deskriptip dan pendekatan studi pustaka dalam memberikan jawaban atas masalah tersebut. Tulisan ini menawarkan pola misi Kristen yang berlandaskan doktrin Allah Trinitas sebagai upaya untuk menangkal radikalisme agama. Pola misi ini melihat misi yang berpusat pada Allah Trinitas dan meninggalkan pola misi yang berlandaskan pada Gereja. Misi ini akan memberikan nilai-nilai toleransi dan akan menjadi tameng dalam menangkal radikalisme agama di Indonesia.